2019
DOI: 10.1007/s10592-019-01172-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative landscape genetics of two endemic torrent salamander species, Rhyacotriton kezeri and R. variegatus: implications for forest management and species conservation

Abstract: Comparative landscape genetic studies provide insights into whether relationships between landscape features and patterns of spatial genetic structure differ among populations, species, habitat types, and regions. For species with fragmented distributions, especially when management practices contribute to fragmentation, tests of the factors structuring population connectivity are particularly important for understanding continued risks. We determined levels of genetic diversity and tested the relationships of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…Richardson (2012) and McCartney-Melstad, Vu, and Shaffer (2018) found both distance and roads shape the genetic structure of wood frogs (Lithobates sylvatius) and Eastern tiger salamanders (Ambystoma tigrinum), which are often sympatric with E. bislineata in northeastern North America. Generally, our results are congruent with other studies that show urbanization affects spatial and population dynamics, as well as genetic structure for a broad range of amphibians (Jean-Marc et al, 2018;Emel, Olson, Knowles, & Storfer, 2019;Marsh et al, 2008;Munshi-South et al, 2013;Scheffers & Paszkowski, 2011;Vanek, King, & Glowacki, 2019;Villasenor, Driscoll, Gibbons, Calhoun, & Lindenmayer, 2017) and other animal taxa (DeCandia et al, 2019;JaffĂ© et al, 2019). Mechanisms underlying the effects of urbanization on amphibian gene flow include physical barriers to dispersal, lack of free-standing water or moist microhabitats, and the presence of extensive light and noise pollution (Eigenbrod, Hecnar, & Fahrig, 2009;Hale et al, 2013 (Holgerson, Lambert, Freidenburg, & Skelly, 2018), and leaves patches of unsuitable terrestrial habitat interspersed among undeveloped, seminatural areas (Hitchings & Beebee, 1997).…”
Section: Urbanization Reduces Genetic Connectivity Between Streams supporting
confidence: 93%
“…Richardson (2012) and McCartney-Melstad, Vu, and Shaffer (2018) found both distance and roads shape the genetic structure of wood frogs (Lithobates sylvatius) and Eastern tiger salamanders (Ambystoma tigrinum), which are often sympatric with E. bislineata in northeastern North America. Generally, our results are congruent with other studies that show urbanization affects spatial and population dynamics, as well as genetic structure for a broad range of amphibians (Jean-Marc et al, 2018;Emel, Olson, Knowles, & Storfer, 2019;Marsh et al, 2008;Munshi-South et al, 2013;Scheffers & Paszkowski, 2011;Vanek, King, & Glowacki, 2019;Villasenor, Driscoll, Gibbons, Calhoun, & Lindenmayer, 2017) and other animal taxa (DeCandia et al, 2019;JaffĂ© et al, 2019). Mechanisms underlying the effects of urbanization on amphibian gene flow include physical barriers to dispersal, lack of free-standing water or moist microhabitats, and the presence of extensive light and noise pollution (Eigenbrod, Hecnar, & Fahrig, 2009;Hale et al, 2013 (Holgerson, Lambert, Freidenburg, & Skelly, 2018), and leaves patches of unsuitable terrestrial habitat interspersed among undeveloped, seminatural areas (Hitchings & Beebee, 1997).…”
Section: Urbanization Reduces Genetic Connectivity Between Streams supporting
confidence: 93%
“…Landcover-based models, on the other hand, always behaved similarly between regions, improving, although slightly, genetic differentiation predictions from IBD models in the ICS and MTR (Table S5). If we consider this together with the fact that forest cover had the highest weight in landcover ENMs (Table S6), our results add to the cumulative evidence that forested areas play a key role in genetic connectivity in salamander populations (Cushman 2006;Antunes et al 2018;Emel et al 2019;Lourenço et al 2019;Arntzen and van Belkom 2020).…”
Section: The Relative Role Of Physical and Ecological Isolation In Genetic Differentiationsupporting
confidence: 57%
“…Implementing resistance models into the analysis can broadly improve the understanding of genetic connectivity in a landscape, and how certain elements can influence connectivity which was also the case for our study. Using the MLPE method a study on two salamander species, Rhyacotriton kezeri and Rhyacotriton variegatus, showed that forest coverage is essential for the dispersal of these species, while fragmentation and deforestation have an overall negative impact on the genetic connectivity [58]. Interestingly, in this study the calculations were separated via clusters and IBD was selected as the most fit model for the northern population clusters.…”
Section: Effects Of Geographic and Resistance Distances On Gene Flowmentioning
confidence: 89%